The influence of geography on Yemen's Red Sea geopolitics and the Houthi maritime insurgency / Khaldoon Ahmed Hasson Abdulla - Khaldoon Ahmed , Hasson Abdulla (2019)
Regardless of Yemen’s historical significance in the construction of the Red Sea identity, contemporary studies of the Red Sea sub-system perceive it as a peripheral and fragile state, so the threat of non-state actors in the country could result in a spillover effect on the region. Meanwhile, Yemen’s geographical factor has been understudied, there is a shortcoming in defining the causal relationship that geography grants Yemen in the Red Sea geopolitics. This fact is evident in the analysis of the current civil war in Yemen, especially the Houthi maritime operations. Given this setting, this study aims to illustrate the influence of geography on Yemen's Red Sea geopolitics and the Houthi maritime insurgency. This study aims to analyze the geographical configuration of Yemen in the context of the Red Sea as a narrow sea, to ascertain how geography influences the causal relationship between Yemen and the Red Sea geopolitics. Building on that, this study aims to analyze the operations of the Houthi maritime insurgency to explore their utilization of Yemen’s geographical factors, and therefore realizing their long-term impacts and strategic objectives. To this end, this study adopts a geopolitical frame of analysis, borrowing from the hypothesis and assumptions of Vego's work 'Naval Strategy and Operations in Narrow Seas' in order to find the causal relationship between the research variables (geography, Yemen's Red Sea geopolitics, and the Houthi maritime insurgency). Accordingly, the study follows a qualitative research method, in which empirical data was collected from primary and secondary resources, coded, and then categorized into themes relevant to the research objectives. These were further analyzed based on the theoretical framework to conclude the findings. Consequently, the research found that the geographical configuration of Yemen grants it a natural influence and a central role in Red Sea geopolitics, which provides a strategic and operational advantage Regardless of Yemen’s historical significance in the construction of the Red Sea identity, contemporary studies of the Red Sea sub-system perceive it as a peripheral and fragile state, so the threat of non-state actors in the country could result in a spillover effect on the region. Meanwhile, Yemen’s geographical factor has been understudied, there is a shortcoming in defining the causal relationship that geography grants Yemen in the Red Sea geopolitics. This fact is evident in the analysis of the current civil war in Yemen, especially the Houthi maritime operations. Given this setting, this study aims to illustrate the influence of geography on Yemen's Red Sea geopolitics and the Houthi maritime insurgency. This study aims to analyze the geographical configuration of Yemen in the context of the Red Sea as a narrow sea, to ascertain how geography influences the causal relationship between Yemen and the Red Sea geopolitics. Building on that, this study aims to analyze the operations of the Houthi maritime insurgency to explore their utilization of Yemen’s geographical factors, and therefore realizing their long-term impacts and strategic objectives. To this end, this study adopts a geopolitical frame of analysis, borrowing from the hypothesis and assumptions of Vego's work 'Naval Strategy and Operations in Narrow Seas' in order to find the causal relationship between the research variables (geography, Yemen's Red Sea geopolitics, and the Houthi maritime insurgency). Accordingly, the study follows a qualitative research method, in which empirical data was collected from primary and secondary resources, coded, and then categorized into themes relevant to the research objectives. These were further analyzed based on the theoretical framework to conclude the findings. Consequently, the research found that the geographical configuration of Yemen grants it a natural influence and a central role in Red Sea geopolitics, which provides a strategic and operational advantage